Understanding Women’s Roles In Agriculture (Study of Women in Dairy And Shallot Farming in East Java) - Mely Noviryani; Wahyu Handayani; Wike; Keppi Sukesi (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2019)
This research studied the roles of women in dairy farming in Ngantang and Karangploso and shallot farming in Pare and Probolinggo, East Java. The objectives were to identify the role and function of women farmers in all stages of dairy and shallot production and to examine the role and level of involvement of women farmers from social and economic aspects, local wisdom and knowledge used on the farm as well as the driving and inhibiting factors of women farmers’ participation. Applying Harvard Analytical Framework, this study identified the division of labor between men and women on the farm, women’s access and control over the benefit of the farm and its influencing factors. The results confirm that women have significant and vital roles in almost all stages of dairy and shallot farming although their roles are mostly related to the construction of women’s roles held generally within Indonesian traditional societies. However, women still have limited access and control over the process of production results from the farm. The inhibiting factors for women’s participation in farming is dominated by psycho-cultural aspect that hinder women’s access to knowledge, information, networks and control over family’s income. Nevertheless, women also show their potential to empower themselves through women groups that can encourage women's awareness in accessing economic resources and knowledge as well as helping them to gain more control over the process of production from the farm.